(untitled) (Journal of the College of Basic Education, 2023)
Contemporary media today is of great importance in influencing audience attitudes. and defining its positions on the various issues revolving around it, as these methods contribute greatly to Forming public opinion, defining its directions, and drawing its perception of what is happening around it and in the world, and in the light of what it presents. Therefore, media academic institutions resort to audience research and studies in order to Media institutions benefit from it as long as the audience is the basis on which the work of these is based. institutions. Talk programs are among the most widespread and successful contemporary media programmes. The informational message to the listeners